Perancangan Sign System Pada Masjid Al-Huda di Kelumpang Dusun VII - John John; Melvin Mirsal; Ibni Aura; Dendy Tri Novarizal; Dian Khalisyah Fazri (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
Mosques are one of the important elements in the structure of Islamic society. For Muslims, mosques have great significance in life, both physically and spiritually. The word Masjid itself comes from the word sajada yasjudu-masjidan which means place of prostration. Every Muslim may pray in any area except over graves, in unclean places and places that according to Islamic law are not suitable for prayer. Sign system is a series of visual representations that aim as a medium of human interaction in public space. Al-Huda Mosque is a public facility used by the community around Dusun VII Kelurahan Kelumpang, but also used by the general public who pass through the area. But Al-Huda Mosque does not have an adequate sign system so that sometimes the general public who cross the area to just ride prayers are sometimes confused to know the facilities contained in the mosque. This study uses 5W + 1H data analysis techniques with the aim that the community around the mosque or the general public who pass through the area know the facilities contained in the mosque. The design results are in the form of stickers and acrylic boards that will be displayed in certain places in Al-Huda Mosque.